Traumatic dural sinus thrombosis causing persistent headache in a child - Lakhkar Bhavana; Lakhkar Bhushan; Singh Brij; Agrawal Amit (Journal of Emergencies, Trauma and Shock, 2010)
Dural venous sinus thrombosis following a mild head injury is increasingly recognized. We report case of a 9-year-old male child presented with progressive headache and vomiting following a minor fall. A diagnosis of sinus venous thrombosis was suspected on nonenhancing computed tomography, and that was confirmed with magnetic resonance venography. The child was managed with intravenous fluids, anticoagulation (injection heparin followed by oral anticoagulants-tab coumarin), antiedema measures (mannitol), and antiepileptics (phenytoin) with good outcome.